2016
DOI: 10.1038/srep27862
|View full text |Cite
|
Sign up to set email alerts
|

Effects of LDL Receptor Modulation on Lymphatic Function

Abstract: Atherosclerosis is driven by the accumulation of immune cells and cholesterol in the arterial wall. Although recent studies have shown that lymphatic vessels play an important role in macrophage reverse cholesterol transport, the specific underlying mechanisms of this physiological feature remain unknown. In the current report, we sought to better characterize the lymphatic dysfunction that is associated with atherosclerosis by studying the physiological and temporal origins of this impairment. First, we asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
67
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(68 citation statements)
references
References 64 publications
1
67
0
Order By: Relevance
“…This concurs with previous findings showing progression stage dependent increases in lymphatic capillary content in human carotid artery plaque1920, and with the recent observation that lymphatic dysfunction precedes the onset of atherosclerosis30. Interestingly, inhibition of VEGFC/D dependent lymphangiogenesis did, in contrast to lymph node/efferent dissection, not affect the atherosclerotic burden, while increasing adventitial and plaque CD3 + T cell content.…”
Section: Discussionsupporting
confidence: 93%
“…This concurs with previous findings showing progression stage dependent increases in lymphatic capillary content in human carotid artery plaque1920, and with the recent observation that lymphatic dysfunction precedes the onset of atherosclerosis30. Interestingly, inhibition of VEGFC/D dependent lymphangiogenesis did, in contrast to lymph node/efferent dissection, not affect the atherosclerotic burden, while increasing adventitial and plaque CD3 + T cell content.…”
Section: Discussionsupporting
confidence: 93%
“…We have recently demonstrated that lymphatic dysfunction, at least in an early stage of atherosclerotic disease, is mainly caused by collecting lymphatic vessel impairment 24. In our current experimental design, as the atherosclerotic plaque is already advanced, we do not exclude the fact that the defect in lymphatic transport could now reside in both the initial and the collecting lymphatic vessels.…”
Section: Resultsmentioning
confidence: 88%
“…Therefore, it is very likely that LEC and platelet signaling pathways depend on the amount of cholesterol in their microdomains, consequently modulating platelet aggregation and adhesion to the lymphatic endothelium. As we hypothesize that apoA‐I plays a positive role in preserving lymphatic transport, the expected repercussion would be observable, primarily, at the level of the collecting lymphatic vessel, the entity that is first defective during atherosclerosis‐associated lymphatic dysfunction 24. By improving lymphatic vessel integrity, we believe that apoA‐I would improve lymph transport per se, thus promoting the movement of lymph content toward the blood circulation.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations